Effect of different morphologies on slow crack growth of high-density polyethylene. Issue 36 (23rd April 2015) - Pan, Yuxi; Gao, Xueqin; Wang, Zhongwu; Lei, Jun; Li, ZhongMing; Shen, KaiZhi
<x xml:space="preserve">Abstract</x> We made different morphologies of HDPE using OSIM to increase the resistance to SCG.